IMPROVING LISTENING SKILL BY ACTIVATING STUDENTS’ PRIOR KNOWLEDGE - Sitti Nurpahmi (ETERNAL (English, Teaching, Learning and Research Journal), 2015)
This research paper aims at finding whether the students ability in listening can be improved by activating students’ prior knowledge. The research conducted at English education study program of faculty of Tarbiyah and education of UIN Alauddin Makassar. This research applied cluster random sampling method. The research data were collected using listening test. It was given at pretest and posttest to know the students’ achievement on listening. The data got during research was analyzed by t test. The finding of the study indicated that the experimental group was higher than that of control group. The result of the hypothesis testing showed that the difference of average score was significant (0.000 < 0.05). This means that there was an improvement of students’ achievement after being exposed by activating their prior knowledge. It implies that activating students’ prior knowledge can improve students’ listening skill.